A production process of gold foil and silver foil pasting on wooden furniture surface
Patent Information
- Application Number
- CN202610963152.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-08-18
AI Technical Summary
[0005]为了解决上述背景技术中提出的技术缺陷,本发明的目的是提供一种木制家具表面贴金箔、银箔的生产工艺,以解决现有技术中边角架桥开裂、银箔附着力差、工艺一致性差的技术问题
1.本发明通过智能化胶水厚度实时反馈控制和边角独立参数调节,彻底解决了传统工艺中边角胶水不均导致的架桥和开裂问题,产品冷热循环测试合格率从原来的70%提升至98%以上。
Smart Images

Figure CN122583199A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of furniture surface decoration technology, specifically to a production process for applying gold or silver foil to the surface of wooden furniture, which is particularly suitable for the production of high-end wooden furniture where adhesion and edge quality are required. Background Technology
[0002] Applying gold or silver leaf is a high-end technique for decorating the surface of wooden furniture, giving the product a metallic luster and luxurious feel. Traditional foil application typically involves steps such as applying a primer, sanding, applying adhesive, applying the foil, drying, and then applying a topcoat. However, traditional methods have the following prominent problems: (1) Bridging and cracking at edges and corners: The adhesive spraying is easily too thick or too thin at the edges, curved surfaces and other parts, causing the gold and silver foil to bridging (arching) or cracking under the hot and cold cycle environment. (2) The adhesion of silver foil is extremely poor: Compared with gold foil, silver foil has low surface energy and high chemical inertness, and its bonding force with conventional PU topcoat is very weak. It is very easy to peel off due to slight scratches during later use. (3) Glue thickness control depends on manual labor: In traditional processes, the thickness and uniformity of glue spraying depend entirely on the experience of the spray gunner, resulting in large quality fluctuations between different batches and different operators; (4) Inadequate drying process: The existing process lacks secondary pressing and staged drying, resulting in insufficient interfacial bonding strength between the adhesive and the foil layer.
[0003] To address the aforementioned issues, existing Chinese patent CN102431369A discloses a process for applying gold / silver foil, comprising the following steps: a) spraying a primer onto the surface to be coated, and after drying, lightly sanding until the surface is free of particles; b) spraying adhesive onto the primer, and after drying, applying the gold / silver foil; c) after foil application, spraying a topcoat; before step a, a layer of gold / silver oil needs to be applied to the surface to be coated; between steps b and c, at least one layer of vinyl primer needs to be sprayed; after the topcoat in step c dries, a dehumidification treatment is performed, and after dehumidification, it is dried under constant temperature conditions to obtain the finished product. Although the gold / silver foil product, after dehumidification and constant temperature drying, will not experience cracking, blistering, or delamination during use, it uses an NC paint system and does not solve the problems of uneven adhesive application at the edges and corners and weak silver foil adhesion.
[0004] Chinese patent CN103614061A proposes a high-adhesion primer with the following composition and weight percentages: 90-95% moisture-curing polyurethane resin; 0.5-1% dehydrating agent; 0.3-0.5% leveling agent; and 4.2-8.5% dehydrated n-butyl acetate. Although the addition of moisture-curing polyurethane resin provides strong adhesion to metal surfaces, this patent only improves the material itself and does not address the issues of coating thickness control, edge parameter adjustment, or silver foil-specific interface enhancement in the foil application process. Therefore, it still cannot solve the problems of edge bridging and silver foil delamination that exist in the mass production of high-end furniture. Summary of the Invention
[0005] In order to address the technical deficiencies mentioned in the background art, the purpose of this invention is to provide a production process for applying gold or silver foil to the surface of wooden furniture, so as to solve the technical problems of edge and corner bridging and cracking, poor adhesion of silver foil, and poor process consistency in the prior art.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A production process for applying gold or silver leaf to the surface of wooden furniture includes the following steps: S1. Primer application and sanding: Spray primer onto the surface of the wooden furniture substrate. After curing, sand with 600-grit sandpaper to ensure that the primer is not sanded through at the edges and corners. S2. Adhesive Spraying and Intelligent Thickness Control: Oil-based or water-based gold foil adhesive is used for spraying. During the spraying process, a laser displacement sensor or optical thickness gauge is used to perform non-contact real-time detection of the wet adhesive film thickness, and the detection data is fed back to the control system of the spraying equipment. The control system automatically adjusts the oil output, spraying speed and spraying trajectory of the spray gun according to the preset target thickness range. At the same time, the system identifies the corner areas of the furniture through edge detection algorithm, and independently increases the oil output of the spray gun in the corner areas or extends the spraying dwell time to ensure that the adhesive coverage of the corners is sufficient and the thickness is uniform. S3. Applying foil and drying: When the glue reaches the surface dry state, apply gold or silver foil to the glued surface, press and adhere it with rags and old newspapers, then let it dry at room temperature for more than 12 hours, then dry it at 45-55℃ for 4-6 hours, and press it again with rags after cooling. S4. Application of Silver Foil-Specific Adhesion Reinforcement Intermediate Layer: If the material being applied is silver foil, then after step S3 and before applying the topcoat, apply an adhesion reinforcement intermediate layer; the intermediate layer is a polyurethane-modified acrylic resin system, and the spraying thickness is controlled at 8-12μm; if the material being applied is gold foil, then omit this step. S5. Topcoat spraying: Use PU full gloss topcoat, spray twice with wet spraying and wet cross-spraying method, each spray viscosity is 11 seconds, after drying, sand it, and then spray the final topcoat according to the design requirements.
[0007] Preferably, in step S2, the weight ratio of the oil-based gold foil adhesive to the thinner is 1:1.15; and the weight ratio of the water-based gold foil adhesive to water is 1:0.1-0.25.
[0008] Preferably, the preset target thickness range in step S2 is: 20-30 μm wet film thickness in the planar area and 30-40 μm wet film thickness in the corner area; the control system adjusts the oil output of the spray gun in real time according to the deviation between the detected value and the target value, with an adjustment accuracy of ±2 μm.
[0009] Preferably, the edge detection algorithm in step S2 is based on machine vision or a preset 3D model, automatically identifying the edges, curved surfaces, and inner corners with angles less than 120° of the furniture, and independently adjusting the spraying parameters for these parts.
[0010] Preferably, after the foil is applied in step S3, the corners and uneven areas are cleaned with a soft cloth dampened with alcohol, and the cleaning time does not exceed 30 minutes.
[0011] Preferably, the polyurethane-modified acrylic resin system in step S4 comprises the following components by weight: 60-75 parts of polyurethane-modified acrylic resin, 10-15 parts of curing agent, 0.3-0.8 parts of leveling agent, 0.5-1 parts of dehydrating agent, and the balance being butyl acetate.
[0012] Preferably, the adhesion-enhancing intermediate layer described in step S4 is flash-dried at room temperature for 5-10 minutes after spraying, and then baked in an oven at 40-50°C for 30-60 minutes to form a chemical bond with the silver foil surface.
[0013] Preferably, the weight ratio of the curing agent to the main paint in the PU full gloss topcoat in step S5 is 1:2 to 1:2.5, and nitrocellulose lacquer system is not allowed to be used as a protective layer or primer.
[0014] Preferably, when the substrate is PU foam material, it needs to be cleaned with thinner first, then baked at 40-45℃ for more than 7 days, then the primer is sprayed, and then steps S1-S5 are performed.
[0015] Preferably, the process must undergo a hot and cold cycle test before formal production: 5 cycles between -5℃ and +25℃, with each temperature point held for 2 hours, and production can only begin after the edges and corners are checked for bridging and cracking.
[0016] In summary, the beneficial effects of the present invention are as follows: 1. This invention completely solves the problems of bridging and cracking caused by uneven glue application at the edges and corners in traditional processes by using intelligent real-time feedback control of glue thickness and independent parameter adjustment at the edges and corners. The pass rate of cold and hot cycle tests of products has been increased from 70% to over 98%.
[0017] 2. The original polyurethane-modified acrylic intermediate layer of this invention, combined with chemical bonding and secondary mechanical compaction, improves the adhesion (cross-cut test) between silver foil and PU topcoat from level 1-2 to level 0, and significantly enhances impact resistance and damp heat resistance.
[0018] 3. The laser thickness measurement and closed-loop feedback of this invention replaces the operation method that relies on the experience of the gunner. The thickness deviation of glue between different batches of products is controlled within ±2μm, which greatly reduces quality fluctuations and improves process consistency and automation level.
[0019] 4. This invention expands the adaptability of foil-applied processes to difficult-to-adhere substrates (such as silver foil and PU foam materials), making high-end decorative effects more stable and durable. Attached Figure Description
[0020] Figure 1 This is a flowchart of the production process for applying gold and silver foil to the surface of wooden furniture according to the present invention; Figure 2 This is a flowchart of step S2 of the present invention; Figure 3 This is a flowchart of step S3 of the present invention; Figure 4 This is a flowchart of step S5 of the present invention. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0022] Those skilled in the art should understand that, in the disclosure of this invention, the terms "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the above terms should not be construed as limiting this invention.
[0023] In the description of this invention, the use of terms such as "a number" means one or more, with "more than" meaning two or more. Terms like "greater than," "less than," and "exceeding" are understood to exclude the stated number, while terms like "above," "below," and "within" are understood to include the stated number. The use of terms like "first," "second," and "third" is merely for distinguishing technical features and should not be construed as indicating or implying relative importance, the number of indicated technical features, or the sequential relationship between indicated technical features.
[0024] The following is in conjunction with the appendix Figures 1-4 The present invention provides a more detailed description of an embodiment of a production process for applying gold or silver foil to the surface of wooden furniture.
[0025] Example 1 (gold leaf application, no intermediate layer, oil-based adhesive, using typical parameters) A production process for applying gold or silver leaf to the surface of wooden furniture, such as... Figures 1-4 As shown, it includes the following steps: Substrate: Solid oak dining table top (1200mm×800mm×18mm).
[0026] Step 1: Primer Application and Sanding: Spray a PU clear primer to a wet film thickness of approximately 100μm. Allow it to dry at room temperature for 4 hours, then bake at 50℃ for 2 hours. After the primer is fully cured, hand sand it with 600# sandpaper, paying special attention to the four corners to ensure that the primer is not sanded through (check with a 100W incandescent bulb under sidelight; there should be no exposed substrate).
[0027] Step 2, Intelligent Adhesive Spraying and Thickness Control: Mix oil-based gold foil adhesive and thinner at a weight ratio of 1:1.15 until homogeneous, achieving a viscosity (Ford Cup 4, 25°C) of 45 seconds. Load the adhesive into the automatic spraying line, which is equipped with: A laser displacement sensor is installed 200mm behind the spray gun to detect the thickness of the wet adhesive film in real time. The control system (Siemens S7-1200 PLC) has a preset target thickness of 25μm for planar targets and 35μm for corner targets.
[0028] During spraying, the spray gun moves at a speed of 400 mm / s, and the spraying pressure is 0.3 MPa. A laser sensor collects thickness data every 50 ms. The control system compares the measured value with the target value; if the deviation exceeds ±2 μm, the spray gun's output is adjusted via a proportional valve. Simultaneously, the system has a pre-stored 3D CAD model of the furniture panel. An edge detection algorithm automatically identifies all edges and internal angles less than 120°, independently increasing the spray gun's output by 15% and extending the single-dwell time by 0.5 seconds for these areas.
[0029] Spray a cross shape (first horizontally, then vertically). The total wet film thickness was measured at 24-27 μm in the planar area and 34-38 μm in the corner area, with no sagging.
[0030] Step 3, Foil Application and Drying: After spraying the adhesive, place it in an environment of 25℃ and 60% relative humidity for 3.5 hours to check the surface dryness of the adhesive. Gently place a 24K gold foil (100mm×100mm) on the adhesive surface, place old newspaper on it, and use a soft rag to evenly press it from the center outwards, ensuring that there are no air bubbles between the gold foil and the adhesive layer. After applying the foil, gently clean the excess adhesive residue and uneven areas with a soft rag dampened with alcohol for 8 minutes.
[0031] Then, place the workpiece at room temperature (25℃) to dry for 15 hours, and then transfer it to a hot air circulating oven (50℃±2℃) to dry for 5 hours. The relative humidity inside the oven should be controlled below 30%. After cooling to room temperature (25℃), press it again with old newspapers and shredded cloth, with a pressing force of about 2-3 kg / cm².
[0032] Step 4, Topcoat Spraying: Use PU full-gloss topcoat (the ratio of main paint, hardener, and thinner is 1:0.45:0.8, adjusted to a viscosity of 11 seconds). Apply two coats using a wet spray and a wet cross-spray technique. After the first coat, flash dry for 3 minutes. After the second coat, allow it to dry at room temperature for 15 hours. Then, lightly sand it with 400-grit sandpaper, and then spray the same PU full-gloss topcoat once more (viscosity 11 seconds, cross-spray once).
[0033] Thermal cycling test: Place the finished product in a thermal shock test chamber (hold at -5℃ for 2 hours, then quickly switch to 25℃ and hold for 2 hours, with a switching time of <5 minutes), and cycle 5 times. After removal, allow it to recover at room temperature for 2 hours, check the edges and corners with a 10x magnifying glass, and test the adhesion using the cross-cut adhesion test.
[0034] Test results: No bridging or cracking at the edges and corners; cross-cut adhesion grade 0 (100% no peeling); uniform gloss on the gold foil surface.
[0035] Example 2 (Silver foil lamination, including intermediate layer, using typical parameters) Substrate: Medium density fiberboard (MDF, size 600mm×600mm×15mm), with a 0.6mm thick white oak veneer on the surface.
[0036] Step 1, Primer Application and Sanding: Same as in Example 1. A PU transparent primer is used, sanded until smooth and free of grain, with no sanding through the edges.
[0037] Step 2, Intelligent Adhesive Spraying and Thickness Control: Water-based gold foil adhesive is diluted with water at a weight ratio of 1:0.2. After stirring evenly, it is allowed to stand for 15 minutes to defoam. Spraying parameters: Target thickness on the plane is 28μm, and the target thickness at the edges and corners is 38μm. After the edge detection algorithm identifies the edges and corners, the amount of adhesive applied is increased by 18%, and the dwell time is extended by 0.6 seconds. The rest is the same as in Example 1. The actual measured thickness on the plane is 27-29μm, and the thickness at the edges and corners is 37-40μm.
[0038] Step 3, Foil Application and Drying: The surface drying time of the adhesive (25℃, 50%RH) is 4 hours. Apply 999 pure silver foil (100mm×100mm), and the pressing, cleaning, and drying processes are the same as in Example 1 (dry at room temperature for 16 hours, dry at 50℃ for 5.5 hours, and press again after cooling).
[0039] Step 4, Construction of Silver Foil-Specific Adhesion Reinforcement Intermediate Layer: Prepare a polyurethane-modified acrylic resin system with the following components (parts by weight): polyurethane-modified acrylic resin: 68 parts; HDI trimer curing agent: 12 parts; leveling agent (BYK-333): 0.5 parts; dehydrating agent (PS-additive): 0.8 parts; butyl acetate: 18.7 parts.
[0040] After mixing thoroughly, let stand for 10 minutes to defoam. Apply the mixture to the silver foil surface using a standard air spray gun, controlling the wet film thickness to 10 μm (adjusted by the number of sprays and the moving speed, and checked online using a wet film thickness gauge). After spraying, flash dry at room temperature for 8 minutes, then bake in a 45℃ oven for 45 minutes. After baking, remove and allow to cool naturally to room temperature.
[0041] Step 5: Topcoat spraying: Same as in Example 1, use PU full gloss topcoat, wet spray twice, wait for it to dry and sand before spraying the topcoat once more.
[0042] Test results: Adhesion (cross-cut test): Grade 0; 3M tape tear test: No silver foil peeled off; Scratching with a fingernail (approximately 5N force, 5 scratches): No peeling on the surface; Thermal cycling test (-5℃) (25℃, 5 cycles): No bridging or cracking at the edges and corners, and no discoloration on the silver foil surface.
[0043] Example 3 (Gold leaf application, water-based adhesive, verification of different mixing ratios) This embodiment is used to verify the process feasibility and product quality of water-based adhesives at the lower and upper limits of the mixing ratio.
[0044] Substrate: Rubberwood solid wood coffee table top (900mm×500mm×20mm), with the same primer and sanding treatment as in Example 1.
[0045] Step 2: Intelligent adhesive spraying (water-based adhesive, two mixing ratios tested separately) Example 3A (lower limit of mixing ratio): Water-based gold foil adhesive and water were mixed at a ratio of 1:0.1 (i.e., 10% water). Viscosity was 72 seconds. Spraying parameters: target thickness on flat surfaces 25 μm, target thickness at corners 35 μm. Actual measured thickness: 24-26 μm on flat surfaces, 34-36 μm at corners. Surface drying time of the adhesive (25℃, 60%RH) was 5.5 hours.
[0046] Example 3B (Upper Limit of Mixing Ratio): Water-based gold foil adhesive and water are mixed at a ratio of 1:0.25 (i.e., 25% water). The viscosity is 38 seconds. Spraying parameters remain unchanged; the measured thickness is 25-27 μm on flat surfaces and 35-38 μm at edges. The adhesive surface drying time is 2.5 hours.
[0047] Steps 3, 4, and 5: Same as in Example 1 (no intermediate layer required for gold foil), only the foil application process is the same.
[0048] Test results:
[0049] According to the results in the table above, water-based adhesives can be applied normally and meet product quality requirements within a ratio range of 1:0.1 to 1:0.25. Lower ratios (higher adhesive concentration) result in longer surface drying time, but no significant difference in adhesion; higher ratios result in faster surface drying, but care must be taken to avoid sagging if the adhesive is too thin. The intelligent thickness control of this invention effectively avoids the risk of sagging.
[0050] Example 4 (Silver foil application, verification of different intermediate layer formulations and thicknesses) This embodiment is used to verify the scope of implementation of the intermediate layer component described in claim 5.
[0051] Substrate: Birch plywood (1200mm×300mm×12mm), primer and sanding treatment are the same as in Example 1.
[0052] Steps 2 and 3: Apply adhesive (oil-based adhesive 1:1.15, parameters same as in Example 1), apply silver foil, and the drying process is the same as in Example 2.
[0053] Step 4: Intermediate layer construction, designing 3 different formulas Example 4A (lower limit of intermediate layer resin content): Polyurethane modified acrylic resin: 60 parts; HDI curing agent: 10 parts; leveling agent: 0.3 parts; dehydrating agent: 0.5 parts; butyl acetate: 29.2 parts. Sprayed wet film thickness: 8 μm. Flash-dry for 5 minutes, bake at 40°C for 30 minutes.
[0054] Example 4B (upper limit of intermediate layer resin content): Polyurethane modified acrylic resin: 75 parts; HDI curing agent: 15 parts; leveling agent: 0.8 parts; dehydrating agent: 1.0 parts; butyl acetate: 8.2 parts.
[0055] Spray a wet film thickness of 12μm. Flash dry for 10 minutes, then bake at 50℃ for 60 minutes.
[0056] Example 4C (Intermediate layer thickness deviation): The formulation of Example 2 was used, but wet film thicknesses of 6 μm (too thin) and 15 μm (too thick) were sprayed for comparison.
[0057] Step 5: Apply PU full gloss topcoat as in Example 2.
[0058] Test results:
[0059] The results showed that excellent adhesion (grade 0) could be obtained when the intermediate layer resin content was 60-75 parts and the wet film thickness was 8-12 μm. When the thickness was less than 8 μm, the adhesion dropped to grade 1. When the thickness was more than 12 μm, sagging or orange peel may occur. Therefore, 8-12 μm is the preferred range.
[0060] Example 5 (Silver foil laminated onto PU foam substrate) This embodiment verifies the processing technology for PU foam material described in claim 9.
[0061] Substrate: PU foam carved decorative lines (800mm in length, 50mm at the thickest point, with complex relief on the surface).
[0062] Pre-treatment: First, thoroughly wipe the surface with a cotton cloth soaked in thinner to remove mold release agent and oil stains, and let it air dry for 30 minutes. Then, place the lines into a hot air circulating oven, set the temperature to 43℃±2℃, and bake continuously for 7 days (168 hours). After baking, remove them and let them cool naturally to room temperature.
[0063] Primer application: Spray PU primer (same as in Example 1). Note that the angle of the spray gun needs to be adjusted to ensure coverage of the embossed recesses. After drying, sand (600-grit sandpaper, hand-sand the recessed surfaces to avoid sanding through). After the primer has cured, check with an incandescent light to ensure there is no exposed substrate.
[0064] Steps 2, 3, 4, and 5: Same as in Example 2 (applying silver foil, including the intermediate layer). During intelligent adhesive spraying, due to the complex shape of the substrate, the edge detection algorithm automatically identifies all edges and concave corners based on the three-dimensional model and independently controls the spraying parameters, successfully achieving uniform adhesive coverage.
[0065] Test results: No bubbles or bridging after foil application; good adhesion between the intermediate layer, silver foil, and topcoat; passed the thermal cycling test (-5℃). After 5 cycles at 25℃, there were no cracks at the edges and raised areas of the relief; the adhesion test was grade 0 using the cross-cut adhesion test.
[0066] Comparative example (without pretreatment and intermediate layer): The silver foil showed multiple delaminations after one hot and cold cycle, with an adhesion level of only 2.
[0067] Example 6 (Intelligent control effect on the edges and corners of large and complex curved furniture) This embodiment is used to highlight the advantages of the intelligent glue thickness control system in solving the problem of corner bridging.
[0068] Base material: solid wood European-style sofa armrests, a total of 3 pieces are made, divided into three groups: Group A (intelligent control of this invention), Group B (traditional manual spraying, experienced gunner), and Group C (traditional manual spraying, ordinary gunner).
[0069] Process: Oil-based gold leaf adhesive is used to apply gold leaf, without an intermediate layer. All other steps are the same.
[0070] Evaluation indicators: Adhesive thickness uniformity: Take 5 points on the plane and 5 points on the corner to measure the wet film thickness, and calculate the coefficient of variation CV = standard deviation / average value × 100%.
[0071] Corner bridging rate after foil application: Use a 10x magnifying glass to inspect all corners and record the percentage of corners with bridging (arching, hollowing) out of the total number of corners.
[0072] Defect rate after thermal cycling: The proportion of corner cracks or bridging checked after 5 cycles.
[0073] Test results:
[0074] Conclusion: The intelligent control system of this invention significantly improves the uniformity of adhesive thickness, especially in the corner areas where the control effect is far superior to manual operation, reducing the bridging rate to below 0.5%, and the defect rate after hot and cold cycling is almost zero.
[0075] Comparative example (traditional process, without intelligent control and intermediate layer) Substrate: MDF board with white oak veneer, as in Example 2.
[0076] Process: Traditional manual spraying of glue is used (by the same skilled sprayer, without thickness feedback control); glue ratio, foil application, and drying are the same as in Example 2, but without the secondary pressing step; no intermediate layer is sprayed before the topcoat; the topcoat uses the NC system (nitrocellulose gloss varnish, sprayed twice).
[0077] Test results: Initial appearance: Multiple glue build-ups are visible at the corners, and bridging occurs after foil application (approximately 25% of the corners). Thermal cycling (-5℃) (25℃, 5 cycles): The bridging rate at the edges and corners increased to 40%, and some silver foil fell off; Adhesion (cross-cut test): Level 1-2 (obvious peeling at the edges and corners); Weather resistance test (simulated sunlight exposure, UV aging for 72 hours): fine cracks appeared in the topcoat, and the silver foil oxidized and turned black.
[0078] Comparative conclusion: Compared with traditional processes, the intelligent control and intermediate layer technology of this invention significantly improves edge quality, adhesion, and weather resistance.
[0079] The embodiments described in this specific implementation are preferred embodiments of this application and are not intended to limit the scope of protection of this application. Identical components are represented by the same reference numerals. Therefore, all equivalent changes made to the structure, shape, and principle of this application should be covered within the scope of protection of this application.
Claims
1. A production process for applying gold or silver leaf to the surface of wooden furniture, characterized in that, Includes the following steps: S1. Primer application and sanding: Spray primer onto the surface of the wooden furniture substrate. After curing, sand with 600-grit sandpaper to ensure that the primer is not sanded through at the edges and corners. S2. Adhesive Spraying and Intelligent Thickness Control: Oil-based or water-based gold foil adhesive is used for spraying. During the spraying process, a laser displacement sensor or optical thickness gauge is used to perform non-contact real-time detection of the wet adhesive film thickness, and the detection data is fed back to the control system of the spraying equipment. The control system automatically adjusts the oil output, spraying speed and spraying trajectory of the spray gun according to the preset target thickness range. At the same time, the system identifies the corner areas of the furniture through edge detection algorithm, and independently increases the oil output of the spray gun in the corner areas or extends the spraying dwell time to ensure that the adhesive coverage of the corners is sufficient and the thickness is uniform. S3. Applying foil and drying: When the glue reaches the surface dry state, apply gold or silver foil to the glued surface, press and adhere it with rags and old newspapers, then let it dry at room temperature for more than 12 hours, then dry it at 45-55℃ for 4-6 hours, and press it again with rags after cooling. S4. Application of Silver Foil-Specific Adhesion Reinforcement Intermediate Layer: If the material being applied is silver foil, then after step S3 and before applying the topcoat, apply an adhesion reinforcement intermediate layer; the intermediate layer is a polyurethane-modified acrylic resin system, and the spraying thickness is controlled at 8-12μm; if the material being applied is gold foil, then omit this step. S5. Topcoat spraying: Use PU full gloss topcoat, spray twice with wet spraying and wet cross-spraying method, each spray viscosity is 11 seconds, after drying, sand it, and then spray the final topcoat according to the design requirements.
2. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, In step S2, the weight ratio of the oil-based gold foil adhesive to thinner is 1:1.15; the weight ratio of the water-based gold foil adhesive to water is 1:0.1-0.
25.
3. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, The preset target thickness range mentioned in step S2 is: 20-30μm wet film thickness in planar areas and 30-40μm wet film thickness in corner areas; the control system adjusts the oil output of the spray gun in real time according to the deviation between the detected value and the target value, with an adjustment accuracy of ±2μm.
4. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, The edge detection algorithm described in step S2 is based on machine vision or a preset 3D model. It automatically identifies the edges, curved surfaces, and inner corners with angles less than 120° of the furniture, and independently adjusts the spraying parameters for these parts.
5. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, After applying the foil in step S3, use a soft cloth dampened with alcohol to clean the corners and uneven areas. The cleaning time should not exceed 30 minutes.
6. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, The polyurethane-modified acrylic resin system described in step S4 comprises the following components by weight: 60-75 parts of polyurethane-modified acrylic resin, 10-15 parts of curing agent, 0.3-0.8 parts of leveling agent, 0.5-1 parts of dehydrating agent, and the balance being butyl acetate.
7. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, The adhesion-enhancing intermediate layer described in step S4 is flash-dried at room temperature for 5-10 minutes after spraying, and then baked in an oven at 40-50℃ for 30-60 minutes to form a chemical bond with the silver foil surface.
8. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, In step S5, the weight ratio of the curing agent to the main paint in the PU full gloss topcoat is 1:2 to 1:2.5, and nitrocellulose lacquer system is not allowed to be used as a protective layer or primer.
9. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, When the substrate is PU foam material, it must first be cleaned with thinner, then baked at 40-45℃ for more than 7 days, then the primer is sprayed, and then steps S1-S5 are performed.
10. The production process for applying gold or silver leaf to the surface of wooden furniture according to claim 1, characterized in that, Before formal production, the process must undergo a hot and cold cycle test: cycling between -5℃ and +25℃ 5 times, holding each temperature point for 2 hours, and only after the edges and corners are checked for bridging and cracking can it be put into production.
Citation Information
Patent Citations
Gold / silver foil plastering technology
CN102431369A
High-adhesion primer for gold / silver foil surfaces and preparation method thereof
CN103614061A